(untitled) (Revista Peruana de Investigación Educativa, 2020)
This theoretical article analyzes the participation of girls, boys and adolescents in schools and education in the educational reform of Enrique Peña Nieto promoted in Mexico between 2012 and 2018. This purpose is relevant because, during the 20th century, there was a tension between acceptance formal participation of the student body in specific issues, under certain modalities, at certain educational levels; and, on the other, the rejection and obstruction of such participation by educational and school authorities. The reform did not promote the participation of the Mexican student body and the tension continued, although it seemed that it would change with the General Law on the Rights of Girls, Boys, and Adolescents of 2014 because it stipulated for the first time the right to participation of these populations in schools and other scopes. But the conception of the right to participation continued to reproduce the protected vision that has been present for years in national legal instruments, such as the Organic Law of Public Education of 1942 and international ones, such as the Convention on the Rights of the Child of 1989. Here The challenges faced by the educational system of the compulsory section are examined so that the student body is recognized as an actor with an agency and as a producer of knowledge. Thus, a brief account of the approach of the Student Voices is presented to identify the scope of the modifications undertaken by the educational reform on student participation and, finally, to understand the differences between participation and the right to participation in schools.